2005
DOI: 10.1614/wt-04-119r
|View full text |Cite
|
Sign up to set email alerts
|

Preemergence and Postemergence Control of Japanese Stiltgrass (Microstegium vimineum)1

Abstract: Preemergence (PRE) and postemergence (POST) herbicides registered for large crabgrass control were evaluated for control of Japanese stiltgrass, an invasive, nonnative C4 annual grass. Benefin plus oryzalin, dithiopyr, isoxaben plus trifluralin, oryzalin, oxadiazon, pendimethalin, prodiamine, or trifluralin applied PRE controlled Japanese stiltgrass 87% or greater 8 wk after treatment. Benefin plus trifluralin, metolachlor, or napropamide applied PRE were less effective (78, 39, and 59% control, respectively).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
40
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 4 publications
5
40
1
Order By: Relevance
“…Gover et al (2003) reported complete (100%) control with pendimethalin at 2 lb/acre, and Derr (1999) reported > 75% control. Quinclorac resulted in < 10% control 4 WAT (Judge et al, 2005a), which is corroborated by Brewer et al (2017). Quinclorac resulted in < 10% control 4 WAT (Judge et al, 2005a), which is corroborated by Brewer et al (2017).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Gover et al (2003) reported complete (100%) control with pendimethalin at 2 lb/acre, and Derr (1999) reported > 75% control. Quinclorac resulted in < 10% control 4 WAT (Judge et al, 2005a), which is corroborated by Brewer et al (2017). Quinclorac resulted in < 10% control 4 WAT (Judge et al, 2005a), which is corroborated by Brewer et al (2017).…”
supporting
confidence: 64%
“…Livestock do not graze Japanese stiltgrass unless there are no alternative forages, such as during a drought (authors' observation). Hand-weeding, mechanical methods, and herbicides are all effective forms of control and reduce seed production when conducted before flowering (Askew and Willis, 2007;Gover et al, 2003;Judge et al, 2005aJudge et al, , 2005bJudge et al, , 2008Ward and Mervosh, 2012). These studies indicate the primary goal of any Japanese stiltgrass management program should be to reduce or eliminate seed input into the soil seed bank as seed is necessary for long-term persistence (Askew and Willis, 2007;Fairbrothers and Gray, 1972;Gover et al, 2003;Mehrhoff, 2000;Ward and Mervosh, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sethoxydim has been shown to control Japanese stiltgrass POST (Gover et al 2003;Jones et al 2004;Judge et al 2005a;Judge et al 2005b), but also controls a broader spectrum of grasses including both annual and perennial grasses (Senseman 2007). When considering how management of Japanese stiltgrass impacts desirable native vegetation such as perennial grasses, perhaps fenoxaprop-P will have fewer nontarget impacts.…”
mentioning
confidence: 99%
“…When considering how management of Japanese stiltgrass impacts desirable native vegetation such as perennial grasses, perhaps fenoxaprop-P will have fewer nontarget impacts. Fenoxaprop-P has also been shown to control Japanese stiltgrass POST (Jones et al 2004;Judge et al 2005a;Judge et al 2005b) and does not injure dicots, rushes (Juncaceae), sedges (Cyperaceae), or most perennial grasses (Poaceae) (Senseman 2007).…”
mentioning
confidence: 99%